Peran Manajemen dalam Pengelolaan dan Pengembangan Ekstrakurikuler Seni Tari di SMA Negeri 2 Koto Kampar Hulu - Putri Sylvi Ravina; Sri Meiweni Basra; Muhammad Fikri; Suaida Suaida (INDO PUBLISHING, 2026)
This study aims to describe the role of school management in the management and development of dance extracurricular activities at SMA Negeri 2 Koto Kampar Hulu. This research employed a qualitative method with a descriptive approach. The data were collected through observation, interviews, and documentation involving the principal, the extracurricular dance instructor, and students participating in the dance extracurricular program. This study applied the management theory of Robbins and Coulter, which consists of four management functions: planning, organizing, directing, and controlling. The findings indicate that the implementation of the management functions planning, organizing, directing, and controlling has not yet been carried out optimally. Efforts to develop the dance extracurricular program include supporting students' performance activities, planning the development of training facilities, and preparing student participation in art activities outside the school. Based on thefindings, it can be concluded that the role of school management in managing and developing the dance extracurricular program needs to be improved through the optimization of management functions so that the program can be implemented more effectively, systematically, and sustainably.